2021
DOI: 10.3390/neurolint13040055
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Developmental and Epileptic Encephalopathies

Abstract: Epileptic encephalopathies often have a genetic etiology. The epileptic activity itself exerts a direct detrimental effect on neurodevelopment, which may add to the cognitive impairment induced by the underlying mutation (“developmental and epileptic encephalopathy”). The focus of this review is on inherited syndromes. The phenotypes of genetic disorders affecting ion channels, metabolic signalling, membrane trafficking and exocytosis, cell adhesion, cell growth and proliferation are discussed. Red flags sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 92 publications
(101 reference statements)
2
4
0
1
Order By: Relevance
“…Many genetic abnormalities were associated with the late onset of ES (beyond 1 year of age). Some genes like ALDH7A1, CDKL5, KCNQ2, KCNT1, NTRK2, STXBP1, UGP2 , and WWOX characteristically had an early infantile‐onset in the current cohort similar to that described previously, while genetic variations in NRROS and SYNGAP1 (2/3) had onset of ES beyond 1 year of life like that reported in most patients with these disorders 10,12–15,21,27 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Many genetic abnormalities were associated with the late onset of ES (beyond 1 year of age). Some genes like ALDH7A1, CDKL5, KCNQ2, KCNT1, NTRK2, STXBP1, UGP2 , and WWOX characteristically had an early infantile‐onset in the current cohort similar to that described previously, while genetic variations in NRROS and SYNGAP1 (2/3) had onset of ES beyond 1 year of life like that reported in most patients with these disorders 10,12–15,21,27 …”
Section: Discussionsupporting
confidence: 82%
“…Some genes like ALDH7A1, CDKL5, KCNQ2, KCNT1, NTRK2, STXBP1, UGP2, and WWOX characteristically had an early infantile-onset in the current cohort similar to that described previously, while genetic variations in NRROS and SYNGAP1 (2/3) had onset of ES beyond 1 year of life like that reported in most patients with these disorders. 10,[12][13][14][15]21,27 Microcephaly, facial dysmorphism, movement disorders, behavioral abnormalities, and non-specific neuroimaging findings were not uncommon in the current cohort, as reported previously with other developmental epileptic encephalopathies. [13][14][15] Therapeutic response to initial hormonal therapy was much higher than that reported in IESS from South Asia, suggesting a relatively better epilepsy outcome in genetic IESS.…”
Section: Phenotypic Features (N = 124) N (%)supporting
confidence: 84%
“…Developmental encephalopathy is a condition of developmental impairment due to a nonprogressive brain condition without frequent epileptic activities. The term “developmental and epileptic encephalopathy (DEE)” used to be described as the coexistence of epileptic encephalopathy and developmental delay [ 3 ], but is now referred to as the condition of two comorbidities developing independently of each other, that is, developmental impairment related to both the underlying etiology and the epileptic encephalopathy, though they might share a common genetic etiology. The genetic etiologies responsible for DEE have been incrementally reported in recent decades, especially after the application of next generation sequencing (NGS) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…27,32 Additionally, taking into account patient 5 and her family history (asymptomatic father; sister with neurological disability and autistic features; and patient 5 with seizures in the neonatal period but normal outcome so far) suggests the hypothesis that other factors, such as the presence of modifier genes that encode channels with direct interactions or that are part of the same pathway, may modulate the penetrance or clinical expression associated with KCNQ2-related disorders. 33 Therefore, gaining a comprehensive understanding of the pathogenic molecular mechanisms underlying KCNQ2 variants and their correlation with clinical phenotypes holds significant implications for the clinical management of patients. It not only aids in accurate diagnosis and prognosis but also paves the way for targeted therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous functional studies have shown that DEE-causing substitutions often induce strong loss-of-function, dominant-negative, or gain-of-function effects, in contrast to SLNE-causing variants associated with haploinsufficiency [ 27 32]. Additionally, taking into account patient 5 and his family history(asymptomatic father; sister with neurological disability and autism features; and patient 5 with seizures in the neonatal period but normal outcome so far), suggests the hypothesis that other factors, such as the presence of modifier genes that encode channels with direct interactions or that are part of the same pathway, may modulate the penetrance or clinical expression associated with KCNQ2-related disorders [33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%